Determining the Relationship Between 11th Students’ Attitude Towards Mathematics and Their Achievement in Mathematics - Syamsuri, Syamsuri; Bahtiar, Ramlan (Technium Social Sciences Journal, 2023)
The aim of this study was to determine the relationship between high school students’ attitudes and their mathematics learning achievement. This study uses a survey method. The population in this study includes is grade 11th student at public senior high schools in Pandeglang Regency and Serang City, Indonesia. Sample of this study is 12 schools that determined by stratified proportional random sampling. Data was collected using a questionnaire and students’ mathematics reports. Analysis of the data used is Spearman rank correlation analysis and chi-square test. The results showed that there was a weak but significant positive relationship between students’ attitudes towards mathematics and mathematics learning achievement. This can indicate that there are some students who have high learning achievement in mathematics tend to have attitudes towards mathematics in the medium or low category